1960
DOI: 10.1063/1.1700949
|View full text |Cite
|
Sign up to set email alerts
|

Proton Magnetic Resonance Spectrum of Propane

Abstract: Exact proton magnetic resonance eigenspectra of the spin Hamiltonian are calculated for a system containing one group of six identical protons and one group of two identical protons. The method of calculation considers each group of identical protons as a composite ``particle'' with fixed total spin, and does not require determination of the explicit form of the zero-order eigenfunctions. The calculated spectra are compared with experimental high-resolution spectra of propane at both 40 Mc and 60 Mc. Thevalues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1962
1962
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…(5) Propane, AtBj. Propane has been the subject of several investigations (9)(10)(11)(12), but these studies have not indicated the ease with which the internal chemical shift and coupling constant can be extracted from the experimental spectrum (Fig. 8(a)).…”
Section: Illustrative Examplesmentioning
confidence: 99%
“…(5) Propane, AtBj. Propane has been the subject of several investigations (9)(10)(11)(12), but these studies have not indicated the ease with which the internal chemical shift and coupling constant can be extracted from the experimental spectrum (Fig. 8(a)).…”
Section: Illustrative Examplesmentioning
confidence: 99%
“…the higher temperature limit (H20)20 cluster corresponding to one M Q -N M R model with a single averaged coupling for the nearest interactions, a composite { 1, 0} particle approach[31] leads to [A]2o(I~= 1)(~2o) being the highest outer IIM) component quasiparticle; for the remaining quasiparticles of the set, recoupled subproblems lose their 5ez0 symmetry on account of the presence of the singtet composite particle(s).Tables 3 and 4contributes towards an analysis of [A]2o(Ii = I) spin system over 3486784401 basis states of this sub-problem of both [CD]2o [3a] and the [H20]2o skeletal aspects of the cage-clathrate protonated exo-hydrate [3 c].…”
mentioning
confidence: 99%